Concept Design of the “Guanlan” Science Mission: China’s Novel Contribution to Space Oceanography - Chen, Ge; Tang, Junwu; Zhao, Chaofang; Wu, Songhua; Yu, Fangjie; Ma, Chunyong; Xu, Yongsheng; Chen, Weibiao; Zhang, Yunhua; Liu, Jie; Wu, Lixin (Frontiers in Marine Science, 2019)
Among the various challenges in spaceborne radar observation of the ocean, the following two issues are probably of a higher priority: inadequate dynamic resolution, and ineffective vertical penetration. It is therefore the vision of the National Laboratory for Marine Science and Technology of China that two highly anticipated breakthroughs in the coming decade are likely to be associated with radar interferometry and ocean lidar technology, which are expected to make a substantial contribution to a submesoscale-resolving and depth-resolving observation of the ocean. As an expanded follow-up of SWOT and an oceanic counterpart of CALIPSO, the planned “Guanlan” science mission comprises a dual-frequency (Ku and Ka) interferometric altimetry (IA) and a near-nadir pointing ocean lidar (OL). Such an unprecedented combination of sensor system has at least three prominent advantages. (i) The dual-frequency IA ensures a wider swath and a shorter repeat cycle which leads to a significantly improved temporal and spatial resolution up to days and kilometers. (ii) The first spaceborne active OL ensures a deeper penetration depth and an all-time detection which leads to a layered characterization of the optical properties of the subsurface ocean, meanwhile serves as a near-nadir altimeter measuring vertical velocities associated with the divergence and convergence of geostrophic eddy motions in the mixed layer. (iii) The simultaneous functioning of the IA/OL system allows an enhanced correction of the contamination effects of the atmosphere and the air-sea interface which in turn considerably reduces the error budgets of the two sensors. As a result, the integrated IA/OL payload is expected to resolve the ocean variability at submeso and sub-week scales with a centimeter-level accuracy, meanwhile to partially reveal the marine life system and ecosystem with a 10-m vertical interval in the euphotic layer, moving a significant step forward towards a “transparent ocean” down to the vicinity of thermocline both dynamically and bio-optically.